DERADIKALISASI MANTAN NARAPIDANA TERORISME: STUDI KASUS MW ALIAS WG - syahputra, edy; Sukabdi, Zora A (Journal of Terrorism Studies, 2021)
A case study of deradicalization of MW aka WG is interesting to explore because of the participation and involvement of TNI personnel or Babinsa (Bintara Pembina Desa) in providing assistance and guidance to former terrorism convicts so that MW aka WG and its community can be disengaged from terrorist group and violent ideologies. UU no. 5 Tahun 2018 has regulated the involvement of the TNI in dealing with acts of terrorism, but so far the implementation rules through the Presidential Regulation have not been ratified so that the involvement of the TNI (Indonesian National Army) cannot be fully operationalized, TNI (Indonesian National Army) unit which has been deployed to the village level (Babinsa) is a huge potential to be used in monitoring and preventing the spread of radicalism and terrorism in the form of deradicalization activities so that former terrorists or ex-convicts do not rejoin terrorist group or spread radical ideas and terrorism for the recruitment of new members of terrorist groups.